1974
DOI: 10.2307/2098314
|View full text |Cite
|
Sign up to set email alerts
|

Technical Change and Scale Economies in an Engineering Production Function: The Case of Steam Electric Power

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Sun* This paper is taken from the author's dissertation written at University of California-Berkeley. The author would like to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This contrasts with the approach taken in econometrics where generation costs, or more typically plant costs, are broken down using a regression model [30,42,7,4,26,49,40,23,27,35,25].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the approach taken in econometrics where generation costs, or more typically plant costs, are broken down using a regression model [30,42,7,4,26,49,40,23,27,35,25].…”
Section: Introductionmentioning
confidence: 99%
“…Support for this hypothesis is found in the decline of the national average heat rate, or BTUs per net KWH, from 16,500 in 1938 to 10,361 in 1978, a decline of 37.12%. Evidence relating the adoption of newer vintaged capital to the reduction in the heat rate is reported in a related study by Cowing [8]. 22 Using an engineering approach, Cowing found that a one unit change in vintage increased thermal efficiency by approximately 2% per annum during 1947-65.…”
Section: Estimates Of the Direction Of Technical Changementioning
confidence: 99%
“…'See Joskow and Rose (1985), Tables 1 and 2. "Li ng (1964), Cootner and Lof (1965), Bushe (1981), Wills (1978), and Cowing (1974) appear to take no account of variations over time, scale and technology in analyzing unit reliability. The EPTI Technical Assessment Guide (1982, B-55) assumes that subcritical and supercritical units of equivalent size have the same reliability.…”
Section: Introductionmentioning
confidence: 99%